EVOLUŢIA SCHIMBĂRILOR ÎN SISTEMUL DE ÎNVĂŢĂMÂNT ŞI CERCETARE ŞTIINŢIFICĂ - USM ADMIN (Moldova State University, 2010)
The modernization of teaching process under its most difficult aspects related to the identification of concept of modernization, to the structural presentation of the concept, to the introduction of a unitary terminology, the issue of development of syllabi is the one which, after being modified, will implicitly lead to the opening of access to inter- national educational structures.